Antibacterial and antiplaque effects of alpinia monopleura herbal toothpaste against streptococcus mutans - Nia Afdilla; Prayoga Ridha Faisal; Musdalipah Musdalipah (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Dental caries remains a prevalent global oral health problem primarily associated with Streptococcus mutans colonization and dental plaque accumulation. Increasing concerns about the prolonged use of synthetic antibacterial agents have prompted the exploration of plant-based alternatives. Alpinia monopleura, an endemic plant from Southeast Sulawesi, contains bioactive phytochemicals with reported antimicrobial activity. This study aimed to evaluate the antibacterial activity and antiplaque effectiveness of herbal toothpaste containing A. monopleura extract against S. mutans. Research Methodology: A quasi-experimental, randomized pre-test and post-test design was conducted involving 64 participants, allocated into two groups: F1 (20% A. monopleura extract) and F2 (30% A. monopleura extract). Antibacterial activity was assessed in vitro using the agar diffusion method against Streptococcus mutans (ATCC 25175). Clinical effectiveness was evaluated by measuring the plaque index before and after a 7-day intervention. Data were analyzed using paired and independent t-tests, followed by multivariate linear regression at α = 0.05. Results: The 30% formulation demonstrated stronger antibacterial activity with a mean inhibition zone of 14.92 mm compared to 6.87 mm in the 20% group. Both formulations significantly reduced plaque index scores. In F1, the mean plaque index decreased from 2.19 ± 0.69 to 1.34 ± 0.48 (p < 0.001), while in F2 it decreased from 2.50 ± 0.51 to 1.84 ± 0.37 (p < 0.001). Multivariate analysis confirmed extract concentration as a significant predictor of plaque reduction. Conclusion: Alpinia monopleura-based herbal toothpaste exhibits significant antibacterial activity against S. mutans and effectively reduces dental plaque. The 30% concentration shows superior antimicrobial potency, supporting its potential development as a natural dentifrice alternative for caries prevention.